Calculation of Effective Earth Radius and Point Refractivity Gradient in UAE - Abdulhadi Abu-Almal; Kifah Al-Ansari (International Journal of Antennas and Propagation)
A large set of 14 years of reliable local radiosonde meteorological data, from 1990 to 2003, has been used to calculate the effective Earth radius and point refractivity gradient in the United Arab Emirates. The obtained values are used to investigate their impact on the design of microwave links. The cumulative distribution of the refractivity gradient in the first 65 meters above the ground surface, the monthly distribution for the median value of the k-factor, as well as their comparison with the ITU-maps are provided. Both experimental and global standard values are applied to specific link budget calculations.